The Role of Electrostatic Interaction between Free Charge Carriers and Counterions in Thermoelectric Power Factor of Conducting Polymers: From Crystalline to Polycrystalline Domains. Issue 6 (28th April 2020) - Shi, Wen; Yildirim, Erol; Wu, Gang; Wong, Zicong Marvin; Deng, Tianqi; Wang, Jian‐Sheng; Xu, Jianwei; Yang, Shuo‐Wang
Abstract: One of the most burning problems in organic thermoelectrics is the lack of deep understanding on the key limiting factors of thermoelectric efficiency at different length scales for conducting polymers. Here, by examining a prototypical π ‐conjugated polymer, poly(3‐hexylthiophene) from molecular level to crystalline and polycrystalline domains, and on the basis of first‐principles calculations, new insights are presented into the thermoelectric transport in conducting polymers, and new material design guidelines are provided. It is proved that in the crystalline domains of conducting polymers, due to the strong electrostatic interactions between free charge carriers and counterions, the power factor within a wide range of doping level is governed by the counterion‐induced electronic scattering. It is corroborated that in the polycrystalline domains, although the short mean free path prevents the holes undergoing grain‐boundary scatterings, the crystallite orientations relative to the conduction path and the grain sizes strongly affect the power factor, leading to the modulation of the power factor by at least two orders of magnitude. Abstract : In the crystalline domains of conducting polymers, due to the strong electrostatic interactions between free charge carriers and counterions, the power factor is governed by the counterion scattering. In the polycrystalline domains, although the short mean free path prevents the holes undergoing grain‐boundary scatterings, the crystallite orientations, and the grain sizes strongly affect the power factor.